ANALISIS SARANA PRASARANA DAN MOTIVASI BELAJAR IPA KELAS VIII SMP ANNUR PEKANBARU - Wela Sukma; Darmawati Darmawati; Arnentis Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Schools as formal education institutions are a means of achieving educational goals through the teaching and learning process. This research was conducted to find out the analysis of facilities infrastructure and motivation learn of natural science in class VIII junior high school of Annur Pekanbaru from April to November 2018. This study was conducted with a sample of eighth grade students totaling 17 students in the 2017/2018 school year using total sampling techniques. The instruments used were questionnaires and observation sheets. Data obtained by distributing questionnaires and direct observation. The data obtained were analyzed descriptively. Analysis of infrastructure in Annur Pekanbaru Middle School obtained an average 68,45% percentage including quite good categories. Analysis of the learning motivation of Grade VIII students at Annur Pekanbaru Middle School was obtained by the average 63,76% percentage including enough categories. Based on the results of the study it can be concluded that with facilities and good learning motivastion it will create a better learning process.Key words: analysis, motivation to learn, facilities and infrastructure